Assessment of Patient Education about Statin Therapy on Quality Measures and Knowledge in an Independent Community Pharmacy - Sean William Clark; Betsy M Elswick; Gretchen K Garofoli (University of Minnesota Libraries Publishing, 2019)
Objectives: The objectives were to 1) assess the possible impact of face-to-face patient education on Electronic Quality Improvement Platform for Plans and Pharmacies (EQuIPP) performance scores, 2) determine if face-to-face patient education increased overall knowledge and number of identified patients on statin therapy, and 3) identify barriers to statin therapy in targeted patients with diabetes. Design:  Participants received an anonymous survey tool collecting demographic data and assessing barriers, baseline knowledge, and perceptions about statin therapy. Following the initial survey, participants received education from the pharmacist describing the risks and benefits of statin therapy and were given a supplemental pamphlet. A second post-education survey tool was given to assess post-education knowledge and perceptions. At the end of the study period, investigators assessed the number of participants started on statin therapy and calculated the predicted percentage change in EQuIPP score. Setting and Participants: This study was conducted at Waterfront Family Pharmacy in Morgantown, West Virginia from December 2017 until April 2018. Participants were included if aged 40 to 75, received at least two fills of a diabetes medication at the pharmacy in the last year, had not taking a statin within a year prior to participating in the study, and could read and write in English. Outcome Measures: The primary outcome measure was the predicted percentage change in the "Statin Use in Diabetes" EQuIPP Score. Secondary measures included post-educational knowledge and perceptions of statin therapy. Results: During the study period, 10 participants completed the surveys and educational intervention. The predicted change in "Statin Use in Diabetes" EQuIPP score was an increase from 75% to 76.9% (+ 1.9%). Prior to the educational intervention, none of the participants could identify a benefit of statin therapy aside from lowering cholesterol. After the intervention, 80% of participants could identify at least one additional benefit of statin therapy. Before the intervention, 30% of participants stated they would consider taking a statin, which increased to 80% following the pharmacist-led education. Lastly, no participants felt they needed to be on statin therapy prior to the intervention. Following the intervention, 40% stated they believed they were candidates for statin therapy. Conclusions: Patients are willing to receive education from pharmacists about their medications and are receptive to general recommendations. A common modifiable barrier to statin therapy is patient knowledge, emphasizing the importance of pharmacist-provided education. Education about statin therapy may also increase EQuIPP scores in an independent community pharmacy, leading to better outcomes for patients and improvement of common performance measures. Overall, it appears patients require more education about statin therapy and the benefit these drugs can provide aside from their cholesterol lowering properties. Pharmacist-provided education regarding statins in patients with diabetes can increase performance measures monitored by third party payers.   Article Type: Original Research